2015
DOI: 10.1007/s40817-015-0005-5
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Functioning in Individuals with Noonan Syndrome: a Systematic Literature Review with Educational and Treatment Recommendations

Abstract: Noonan syndrome (NS) is a relatively common genetic syndrome with variable features including short stature, congenital heart disease, distinctive facial characteristics, skeletal anomalies, and varying degrees of developmental delay. NS is caused by gene mutations in a cellular signaling pathway that is essential for typical growth and development. Research in the past few decades has revealed that individuals with NS have highly variable neurocognitive and behavioral outcomes. To a certain extent, variabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 105 publications
(196 reference statements)
1
27
1
Order By: Relevance
“…Increasing evidence also suggests that while the majority of children with Noonan syndrome function in the general education setting, reduced executive functioning and high rates of ADHD are often present. [30, 31] Children with cardiofaciocutaneous syndrome may have similar facial, growth, and cardiac features but typically have more severely affected cognitive status. [32] Children with Costello syndrome have cognitive issues that fall on a spectrum between Noonan syndrome and cardiofaciocutaneous syndrome; developmental delay or intellectual disability is present in all individuals.…”
Section: Genetics Causes Of Chdmentioning
confidence: 99%
“…Increasing evidence also suggests that while the majority of children with Noonan syndrome function in the general education setting, reduced executive functioning and high rates of ADHD are often present. [30, 31] Children with cardiofaciocutaneous syndrome may have similar facial, growth, and cardiac features but typically have more severely affected cognitive status. [32] Children with Costello syndrome have cognitive issues that fall on a spectrum between Noonan syndrome and cardiofaciocutaneous syndrome; developmental delay or intellectual disability is present in all individuals.…”
Section: Genetics Causes Of Chdmentioning
confidence: 99%
“…Because only patients were included who could complete the MMPI-2-RF, the sample consisted of relatively more patients with higher IQ scores-hence more patients with a mutation in SOS1. Other studies also found patients with a mutation in SOS1 to have more favourable outcomes regarding intellectual functioning than patients with PTPN11 (Pierpont, 2016). Furthermore, patients with psychological or cognitive problems may be overrepresented in this study, because they could be more inclined to participate or were more likely to bereferred for neuropsychological assessment, which might have consequences for the generalization of the findings of this study to the general NS population.…”
Section: Discussionmentioning
confidence: 68%
“…Regarding cognitive functioning, NS is associated with varying degrees of developmental delay and intelligence scores tend to vary from intellectual disability to superior levels of functioning. However, most patients with NS show intellectual abilities within the (low)average range (Pierpont, 2016). In children and adolescents with NS, cognitive difficulties in language functioning, visual processing, motor abilities, attention and executive functioning, memory and social functioning have been found (Pierpont, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intellectual disability is reported in approximately 90–100% CFC patients [Kavamura et al, ; Yoon et al, ] but only 6–23% of NS patients [van der Burgt et al, Pierpont et al, ]. While children with NS rarely have severe intellectual impairments, milder neuropsychological concerns are often evident, especially within particular aspects of learning and memory, attention regulation, or social development [Pierpont, ].…”
Section: Discussionmentioning
confidence: 99%